The court - Coughlin, William J. (William Jeremiah) (New York : St. Martin's Paperbacks, 1999)
Washington attorney Jerry Green discovers that the outcome of four history-making cases rests in the hands of a Supreme Court Justice who is barely being kept alive by machines in a private hospital, and he risks his career trying to force the President do something about it.
National College of Business and Arts
Keywords: Legal stories; Fiction